Phytochemical Screening of Phaleria macrocarpa (Scheff.) Boerl.) and Antibacterial Activity Test of Ethanol Extract Against Staphylococcus aureus Bacteria - Rizki, Muhammad; Harahap, Urip; Sitorus, Panal (Publisher Cv. Inara, 2023)
Phaleria macrocarpa is known as one of the medicinal plants in Indonesia. Almost all parts of the plant have chemical content that is useful for being used as medicine. The growing use of crown plants by the community for various diseases requires a series of tests to obtain traditional medicine preparations that are safe for human use. The purpose of this study was to identify the content of secondary metabolite compounds (alkaloids, flavonoids, saponins, tannins, steroids, triterpenoids, and glycosides) and the antibacterial activity of Staphylococcus aureus with the good method because the good method has the advantage that it is easier to measure the area of the inhibition zone formed because an antibacterial activity is not only on the upper surface of nutrient agar but also at the bottom. The results of phytochemical screening showed that the flesh of Phaleria macrocarpa (Scheff). The results of testing the antibacterial activity of an ethanol extract of crown Phaleria macrocarpa (Scheff) fruit flesh (Boerl) were positive for alkaloids, flavonoids, glycosides, saponins, tannins, and steroids. Boerl.) showed effective results at a concentration of 40 mg/ml against Staphylococcus aureus bacteria with an inhibition zone diameter of 14 mm; the antibacterial activity was categorized as strong.